2004
DOI: 10.1007/s00330-004-2275-7
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative breast MRI in patients with invasive lobular breast cancer

Abstract: To investigate the use of MRI in preoperative characterization of invasive lobular breast cancer (ILC) and in detection of multifocal/multicentric disease. We retrospectively reviewed T1-weighted FLASH 3D precontrast and postcontrast MR images together with subtraction images of 26 women with histopathologically proven invasive lobular cancer. Two experienced radiologists described tumor patterns of ILC independently. MR findings of unifocal, multifocal, single quadrant and multiquadrant disease were correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 35 publications
4
56
0
3
Order By: Relevance
“…Many studies have shown that preoperative MRI changes the surgical approach in 22-44% of patients [11][12][13][14][15][16][17][18], and as mentioned before, in 12-33% of patients this change is a conversion from BCS to mastectomy [11,13,16,[19][20][21][22]. Based on few reported findings, this rate of therapy change is balanced by a conversion rate in the opposite direction of approximately 5% [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that preoperative MRI changes the surgical approach in 22-44% of patients [11][12][13][14][15][16][17][18], and as mentioned before, in 12-33% of patients this change is a conversion from BCS to mastectomy [11,13,16,[19][20][21][22]. Based on few reported findings, this rate of therapy change is balanced by a conversion rate in the opposite direction of approximately 5% [11].…”
Section: Discussionmentioning
confidence: 99%
“…The technique is superior to conventional imaging methods in staging ILC [11][12][13][14][15][16][17][18], which is mainly achieved by improving tumor delineation and detection of additional tumor foci.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show that MRI can even depict ductal carcinoma in situ (DCIS) ( fig. 1) and invasive lobular carcinoma with high sensitivity [17][18][19][20]. To avoid false-positive enhancing lesions and subsequent unnecessary breast biopsies, breast MRI should be only used for certain indications.…”
Section: Current Indications Of Dce Breast Mrimentioning
confidence: 99%
“…The reported false negative rate in fine needle aspiration (FNA) of ILC ranges from 15% to w60% with a sensitivity of 60.5-76%, considerably lower than that of IDCs (Schelfout et al 2004). A false negative core biopsy is also more likely because of the difficult in the localization of the lesions and the sparse cellularity of the tumour (Pointon & Cunningham 1999).…”
Section: Fine Needle Aspirationmentioning
confidence: 99%